Detection of Immunoglobulin G to Poliovirus in Children 5-10 Years Old in Minna, Nigeria - Enejiyon, Sherifat Ozavize; Wuna, Muhammad Muhammad; Babayi, Hafsat; Adabara, Nasiru Usman (Darul Yasin Al Sys, 2024)
In the Minna, data on the seroprevalence rate of antibodies to poliovirus serotypes which can be used to determine children’s immune status and the vaccine efficacy against poliomyelitis is sparse. This study aim was to detect immunoglobulin G to poliovirus in children aged 5-10 years old in Minna, Nigeria. About 2 mL of blood was collected by venipuncture from 91 children selected randomly from various health care facilities across Minna. Blood samples were centrifuged to obtain the sera. The detection of poliovirus specific immunoglobulin G (IgG) was done using polyclonal Enzyme linked immunosorbent assay (ELISA) detection test kits. In this study, all the children had detectable level of antibodies, 85 (93.4%) children consisting of 49 (53.8%) males and 36 (39.6%) females showed protective level of antibodies (seropositive). Seropositivity rate of 96.8% (30/31), 94.0% (31/33) and 88.9% (24/27) was recorded among children aged 9-10, 7-8 and 5-6 years old respectively. About 74.7% (68/91) of the participants were weak responder (concentration of antibodies <50 U/mL) to the vaccines received with low seroconversion rates while 6.6% (6/91) of the children had sub-protective level of antibodies (seronegative). Age, sex, parents’ occupation, mothers’ educational status and drinking water source had no significant association (p>0.05) with seroprevalence rates while fathers’ educational status showed significant statistical association with seroprevalence rate (p<0.05). High seropositivity was recorded in this study, nation-wide seroprevalence is recommended to comprehensively evaluate the progress made so far in sustaining polio-free status.